Analisis Kinerja Mesin Band Saw Soft Mill Menggunakan Total Productive Maintenance Pada PT. Alis Jaya Ciptatama - Evan Febrianto (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
PT Alis Jaya Ciptatama is one of the furniture manufacturers. The band saw soft mill production machine used will experience damage and decrease in performance as the machine ages. The process of changing bearing sets requires 40 hours of downtime in one band saw soft mill machine per year. In addition, there is also a downtime in the process of replacing a broken saw which takes 124 hours per year. This study is to measure the effectiveness of the machine by using the overall equipment effectiveness (OEE) method. The object of this research is a band saw soft mill machine which is a wood cutting machine. The results of the effectiveness measurement show that the average availability value is 96.17%, performance efficiency is 82.15% and the rate of quality is 86.93% so that the OEE value is 68.8%. The OEE value does not meet the requirements of the ideal OEE standard, which is 85%. Then improvements were made by measuring the six big losses to determine the contribution of each loss.Based on the analysis using FMEA, the largest RPN value for the breakdown losses category is 336 for the hilarious bearing failure type and for the reduced speed losses category, which is 140 for the reduced engine speed failure type. Overcoming failures on funny bearings is to carry out preventive maintenance on a regular basis once a week.